COMPARISON OF COPROOVOSCOPIC DIAGNOSTIC METHODS OF V. N. TRACH, MCMASTER AND MINI-FLOTAC FOR HENS’ INFESTATION WITH ASCARIDIA GALLI AND TRICHOSTRONGYLUS TENUIS - Kruchynenko, O. V. (Scientific Progress & Innovations, 2021)
One of the most common gastrointestinal invasions in poultry is ascaridiosis caused by Ascaridia galli and trichostrongylosis (Trichostrongylus tenuis pathogen). In veterinary practice, quantitative coproovoscopic diagnostic methods with a counting chamber are widely used. These methods are important in studying the infestation of poultry with nematodes. However, basic knowledge about the effectiveness of commercial diagnostic methods of poultry in comparison with the method of V. N. Trach is practically absent in the scientific literature. The aim of the study was to compare the effectiveness of V. N. Trach's method and commercial methods: a modified McMaster's with the sensitivity of 50 eggs in 1 g of feces (EGF) and Mini- Flotac in combination with Fill-Flotac (sensitivity 10 EGF) for hens’ infestation with A. galli and T. tenuis. The paper presents the results of testing the above mentioned methods with saturated solutions of: ammonium nitrate (NH4NO3; PT=1.3) for V. N. Trach”s method and sodium chloride (NaCl; PT=1.2) for McMaster’s method and Mini-Flotac. 25 samples of feces 10 g in each were taken on the floor from hens aged 9–12 months on a private farm, located in the village of Shcherbani of Poltava district. Laboratory studies were conducted in the Scientific Laboratory of the Department of Parasitology of Poltava State Agrarian Academy. For V. N. Trach's method, 2.5 g of feces were taken and 47.5 ml of NH4NO3 solution were added, after which it was allowed to stand for 45 minutes. In order to diagnose using the modified McMaster's method, 2 g of feces were taken and 28 ml of saturated brine were added. To conduct examination applying Mini- Flotac method, 2 g of feces were placed in Fill-Flotac and 38 ml of NaCl solution were added according to the exotic animal study protocol. The studies by McMaster's and Mini-Flotac methods were performed 10– 12 minute after the chambers were filled. It has been found that McMaster's method is the most effective in detecting nematode eggs in poultry. On the average, applying the McMaster's method, by 83.3 % more Ascaridia galli eggs and by 80.24 % more Trichostrongylus tenuis eggs were detected than at the V. N. Trach's method (P<0.001). It has been established that V. N. Trach's method had poor correlation dependence in detecting ascaridia and trichostrongyluses eggs in comparison with both the “gold standard” (McMaster's method) and Mini-Flotac. At the same time, when counting A. galli eggs in 1 g of faeces, the Lin's consistency correlation coefficient between the methods of McMaster and Mini-Flotac was significant (CCC=0.96), and at counting T. tenuis eggs it was moderate (CCC=0.91).